Simulation and test on the operation process of an intermittent film-picking component on full-film mulched double ditches - Dai, Fei; Wang, Feng; Guo, Wenjuan; Shi, Rujie; Xin, Shanglong; Liu, Xiaolong; Zhao, Wuyun (International Journal of Agricultural and Biological Engineering, 2024)
In view of the problems in operation process of fixed rake-type residual recycling component, such as poor individual profiling effect in film picking, easy clogging of the compound of films, soil and corn stubbles, high power consumption in film picking, and strong disturbance to seedbed soil, in this study, an operation model of intermittent film-picking on full-film mulched double ditches was proposed and an intermittent film picking component was designed. The DEM-MBD coupled algorithm was adopted for numerical simulation on the operation process of the intermittent film-picking component on full-film mulched double ditches, and a comparative analysis was carried out on the seedbed disturbance effect and resistance variation characteristics in film-picking by fixed and intermittent film-picking components. By taking the forward speed in film-picking, cam arrangement angle of the film-picking component and rotating speed of the cam shaft as independent variables, film-picking rate as the response value, a mathematical model between test factors and the film-picking rate was established, to explore the influence order of the factors on film-picking rate, and the optimal working parameters of the intermittent film-picking component were obtained as follows: the forward speed in film-picking was 2 km/h, cam arrangement angle was 180°, rotating speed of the cam shaft was 120 r/min. Under the optimal parameter combination, the average film-picking rate of the simulation test was 96.1%. Field test showed that, the average film-picking rate of the intermittent film-picking component was 95.6%, and 0.5% higher than that of the simulation test. The working condition of the sample machine was basically consistent with the simulation process, and can accurately represent the operation mechanism of intermittent film-picking on full-film mulched double ditches, showing that the established discrete element simulation model and its parameters were accurate and reasonable. Key words: full-film mulched double ditches, residual film recovery, intermittent film-picking component, DEM-MBD, parameter optimizationDOI: 10.25165/j.ijabe.20241701.8348Citation: Dai F, Wang F, Guo W J, Shi R J, Xin S L, Liu X L, et al. Simulation and test on the operation process of an intermittent film-picking component on full-film mulched double ditches. Int J Agric & Biol Eng, 2024; 17(1): 99-108.